Pengaruh Ketimpangan, Investasi dan Inflasi Terhadap Pertumbuhan Ekonomi di Negara-Negara ASEAN - Iqbal Nurdian Syahputra, Ravi; Titis Kusuma Wardani, Dyah; Sri Wahyudi Suliswanto, Muhammad (VISA: Journal of Vision and Ideas, 2024)
This research presents an analysis of income inequality and economic development in ASEAN countries. This research uses current economic data to identify factors that contribute to income inequality in the context of economic development in the ASEAN region. This analysis includes an understanding of the role of economic policy, the main sectors that influence inequality, and the socio-economic impacts that arise as a result of this inequality. The results of this research have important relevance in efforts to achieve sustainable and inclusive economic development in ASEAN